P91 Post-operative pain in neurosurgery. Issue 3 (14th February 2019) - Haigh, PM; Al-Hatimi, F; Stewart, H; Rajagopal, S; Khalifa, S; Smart, J
Abstract : Objectives: Are the analgesic guidelines for those neurosurgical operations associated with major and complex major pain consistently followed? Is there a correlation between adherence and post-operative pain? Design: Patients undergoing spinal surgery and foramen magnum decompressions were visited on the first post-operative day (D1). They provided their pain score subjectively (0=nil; 10=worst ever experienced); objectively we recorded whether they could move in/out of bed without pain limitation. Subjects: n=57 consecutive patients undergoing elective major and complex major pain neurosurgery between April and June 2018 at the NHNN, Queen Square. Methods: A proforma was completed on D1. The patients consented to take part and answered three questions. We examined what (if any) analgesics they were admitted on, and what had been prescribed to cover the post-operative period. This was compared against the appropriate guideline for that category of operation. Results: Guidelines were only followed in 16/57 (28.1%) cases; not followed in 41/57 (71.9%). On an unpaired T-test: 2-tailed P value=0.0195. Where guidelines were followed, the mean pain score reported was: 3.75 (SD 2.72) Where not followed, the mean pain score was 5.46 (SD 2.29). So with a 95% confidence interval −3.41 to −0.29, there is a significant difference between the pain in those prescribed according to the guidelines and those that were not. Conclusions: The pain guidelines are not routinely followed. Most commonly this was due to no prescription for a non-steroidal anti-inflammatory agent. We suggest regular sessions of education of the guidelines. Cycle 2 closed the loop of the audit. We re-reviewed adherence and pain scores and found guidelines were followed in 34% of cases, which represented a 6% improvement. On a paired two-tailed P value=0.0794. The mean pain score where guidelines were followed=3.42 (SD1.62) against a mean=4.74 (SD 1.89) where guidelines were not followed.